The Influence of Game Addiction and Internet Addiction among University Students on Depression Stress and Anxiety Mediated by Self-regulation and Social Support - Varma, Parvathy; Cheasakul, Uree (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2016)
The present study investigated the direct and indirect influences of Internet and online game addiction on the levels of depression, anxiety, and stress mediated by self-regulation and social support among students of a private university in Thailand. The study’s sample consisted of 380 students of whom (218 females and 162 males) from a private university. Results from the path analysis indicated that the respondents’ level of game addiction and internet addiction had both direct and indirect influences on their levels of depression, anxiety, and stress. The findings were discussed in relation to the significance of self-regulation among university students and the level of social support provided by the University. ผลกระทบของการติดเกมและการติดอินเตอร์เน็ตที่มีต่อภาวะซึมเศร้า ความวิตกกังวล และความเครียดของนักศึกษาที่มีระดับการควบคุมตัวเองและการสนับสนุนทางสังคมที่แตกต่าง งานวิจัยครั้งนี้เป็นศึกษาผลกระทบทั้งโดยตรงและโดยอ้อมของการติดเกมส์และติดอินเตอร์เน็ตต่อภาวะซึมเศร้า ความวิตกกังวล และความเครียด โดยมีปัจจัยเกี่ยวกับการควบคุมตัวเองและการสนับสนุนของสังคมมาเป็นตัวกลาง โดยศึกษาจากนักศึกษามหาวิทยาลัยเอกชนแห่งหนึ่ง จำนวน 380 คน ซึ่งเป็นชาย 162 คนและหญิง 218 คน ผลการวิเคราะห์ข้อมูลพบว่าระดับของการติดเกม และการติดอินเตอร์เน็ตมีผลกระทบทั้งทางตรงและทางอ้อมอย่างมีนัยสำคัญต่อระดับความซึมเศร้า ความวิตกกังวล และความเครียด ผลการวิจัยยังแสดงให้เห็นว่า การควบคุมตัวเองและการสนับสนุนจากสังคมเป็นปัจจัยที่ส่งผลอย่างมีนัยสำคัญต่อผลกระทบของการติดเกมส์และการติดอินเตอร์เน็ตต่อปัจจัยทางจิตวิทยาข้างต้น